Sequential epiretinal membrane removal with internal limiting membrane peeling in brilliant blue G-assisted macular surgery. Issue 10 (31st July 2010) - Schumann, Ricarda G; Gandorfer, Arnd; Eibl, Kirsten H; Henrich, Paul B; Kampik, Anselm; Haritoglou, Christos
Abstract : Purpose: To assess the selectivity of brilliant blue G (BBG) staining by analysing the morphological components of unstained and stained tissue obtained during epiretinal membrane (ERM) removal with internal limiting membrane (ILM) peeling in BBG-assisted macular surgery. Methods: Twenty-six surgical specimens were removed from 13 eyes with epiretinal gliosis during vitrectomy using BBG for ERM and ILM peeling. We included eyes with idiopathic macular pucker, idiopathic macular hole and vitreomacular traction syndrome. The dye was injected into the fluid-filled globe. Unstained and stained epiretinal tissue was harvested consecutively and placed into separate containers. All specimens were processed for conventional transmission electron microscopy. Results: The first surgical specimen of all eyes showed no intraoperative staining with BBG and corresponded to masses of cells and collagen. The second surgical specimen demonstrated good staining characteristics and corresponded to the ILM in all patients included. In seven eyes, the ILM specimens were seen with minor cell proliferations such as single cells or a monolayer of cells. Myofibroblasts, fibroblasts and astrocytes were present. In five cases, native vitreous collagen fibrils were found at the ILM. In six of the eyes, ILM specimens were blank. Conclusion: Our clinicopathological correlation underlines the selective staining properties of BBG. The residual ILM is selectively stained by BBG even when a small amount of cells and collagen adheres to its vitreal side. To reduce the retinal exposure to the dye, the surgeon might choose to remove the ERM without using the dye, followed by a BBG injection to identify residual ILM.